Experimental studies to improve IC engine performance through magnetization of fuel mixture of gasoline and bioethanol - Tatun H Nufus; Dianta M Kamal; Ridwan, Emir; Ridlwan, Hasvienda M; Kusumastuti, Sri Lestari; Apriana, Asep; Juna, Haidir; Todaro, Muhammad; Sapriyanto, Agus; Prasetio, Bayu; Ilham, Rifki Nur (Creative Science, 2022)
Research related to the magnetization of fossil fuels is currently believed to be able to improve the quality of combustion due to the cluster decluster effect on the fuel. Fossil fuels are finite and non-renewable. Meanwhile, non-fossil energy, especially bioethanol, despite having more environmentally friendly exhaust gas emissions and higher octane rating than gasoline, has a lower calorific value than gasoline. To overcome this deficiency, the fuel magnetization of a mixture of gasoline and bioethanol is carried out. The fuel is used in 4 stroke injection motorcycles. Furthermore, the performance of the 4-stroke injection motorcycle was observed. the fuel mixture without magnetization was used as a control variable. The intensity of the electromagnetic field used is less than 2,000 Gauss, this is different from previous analysts. As a result, the magnetized motorcycle experienced an increase in torque of 4.48 – 7.30%, power of 4 – 9.90%, and a decrease in SFC of 6 – 9.20%.